SPREADING OF A DENTAL PATHOLOGIES IN DOGS UNDER THE VETERINARY CLINICS CONDITIONS IN POLTAVA - Мірзаєва, М. С. (Scientific Progress & Innovations, 2014)
The results of the analysis report documentation, spreading of dental diseases, under the veterinary clinics conditions in Poltava for the period 2011 – 2013 years. Considered nosoological form manifestations of pathology and breed of dogs. Proven that dental diseases are quite spread in dogs, they account for 21.11 % from surgical diseases. Obtained data demonstrate the necessity for improvements and additions to existing methods for prevention and treatment the oral cavity diseases in dogs.